Body composition in long-term users of depot medroxyprogesterone acetate. Issue 3 (August 2016) - Modesto, Waleska; Orlandi, Laura T.; Bahamondes, Maria V.; Bahamondes, Luis
Abstract : Objective: The aim of this study was to assess body composition (BC) among depot medroxyprogesterone acetate (DMPA) users and compare this with copper-intrauterine (Cu-IUD) users with up to 15 years of uninterrupted use. Study design: This was a cross-sectional study. Patients and methods: We evaluated BC in women (18–40 years of age) using dual X-ray absorptiometry. Results: At the end of the first 37 years of use, the mean weight was 64.4±8.5 kg in DMPA users, a nonsignificantly higher mean compared with 59.9±6.4 kg among the Cu-IUD users ( P =0.069). The mean of fat mass were 39.0±7.1 and 38.7±4.8% ( P =0.898) and the lean mass were 35.8±2.7 and 33.2±2.8 kg ( P =0.005) in DMPA/Cu-IUD users, respectively. Conclusion: At long-term use of both methods, the BC did not show significant differences. Furthermore, DMPA users did not show significant differences in weight gain or increased lean and fat mass compared with Cu-IUD users.